2021
DOI: 10.12669/pjms.37.3.3943
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the implant diameter on the initial-stability of narrow- and standard-diameter implants placed in simulated Type-I and Type-IV bone-blocks

Abstract: Objective: A comparison of the initial stability of narrow- and standard-diameter implants (SDIs) placed in Type-I and Type-IV bone-blocks is not yet reported. The aim was to evaluate in-vitro the influence of implant diameter on the initial stability of narrow- and standard-diameter implants (SDIs) placed in simulated Type-I and Type-IV bone-blocks. Methods: The present experimental in-vitro study was performed between July and September 2020 at the Specialist Dental Practice, Riyadh, Saudi Arabia. Narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In another study it was also reported that the narrow diameter and standard diameter implants show comparable initial stability, which supports the findings of the current study. 19 In yet another study no significant differences were reported in narrow, regular, and wide diameter implants success after 1-year and 3-year follow-ups. 20 One more study used 4.1mm & 4.8mm diameter implants and observed that ISQ values at baseline and at 4,8, and 12 weeks for both diameters did not differ.…”
Section: Discussionmentioning
confidence: 89%
“…In another study it was also reported that the narrow diameter and standard diameter implants show comparable initial stability, which supports the findings of the current study. 19 In yet another study no significant differences were reported in narrow, regular, and wide diameter implants success after 1-year and 3-year follow-ups. 20 One more study used 4.1mm & 4.8mm diameter implants and observed that ISQ values at baseline and at 4,8, and 12 weeks for both diameters did not differ.…”
Section: Discussionmentioning
confidence: 89%
“…1 Patients tend to ignore the disease due to its lack of specific symptoms, and often suffer from bone defects as the disease progresses and the inflammatory response spreads. 2 In the case of severe periodontitis with bone defects, patients are exposed to the risk of tooth insufficiency and even tooth loosening, which seriously affects their quality of life.…”
Section: Introductionmentioning
confidence: 99%